HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG PERAWATAN TALI PUSAT BAYI BARU LAHIR DENGAN LAMANYA PELEPASAN TALIPUSAT PADA BAYI BARU LAHIR DI PRAKTEK BIDAN DELPI SARAGIH TAHUN 2021 - Stefani Anastasia Sitepu; Vitrilina Hutabarat; Gf Gustina Siregar; Marlen Sadrina Sitepu (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2021)
Background: the Ministry of Health has implemented various programs related to maternal and child health and one of them is prevention of neonatal tetanus and newborn care including umbilical cord care (WHO). , 2017). about newborn umbilical cord care and the length of umbilical cord detachment in newborns at the Delpi Saragih Midwife Practice. Methods: This study subjects were postpartum mothers who had newborns until the umbilical cord was separated at the Delpi Saragih Midwife Practice. Sampling technique with Total Sampling of 35 respondents with measuring instruments, namely questionnaires and observation sheets, data analysis using Chi-Square The results of the study: the level of knowledge of mothers about newborn umbilical cord care showed that of the 35 respondents, most of the respondents had good knowledge, namely 14 people (40.0%), and a small proportion of respondents had sufficient knowledge, namely 9 people (25.8%). With the length of the release of the umbilical cord in newborns, most respondents were normal 5-7 days in releasing the umbilical cord in newborns, as many as 15 people (42.9%), and a small proportion of respondents were fast < 5 days and long > 7 days in releasing the cord. center for newborns as many as 10 people each (28.6%). The results of the Chi-Square analysis show that the value of p = 0.020 <α = 0.05 Conclusion: There is a relationship between the level of knowledge of the mother about newborn umbilical cord care and the length of time the newborn's umbilical cord is released.